Peningkatan Afeksi Anak Usia Dini melalui Dongeng dengan Alat Peraga - Muhammad Wahyudi (Jurnal Abdi Mas Adzkia, 2020)
Through the Fairy Tale Method with props, where children are invited to develop their own children's affections. Furthermore, teachers play a role in orienting children to understand the moral messages contained in, a fairy tale that is conveyed by using a media that is more interesting, so that images that can enhance children's affection in the process carried out in Early Childhood Class Yasmin TK DR. Cipto Mangunkusumo, Bandar Jawa Village, Bandar District, Simalungun Regency. To obtain data through testing and observation with data collection tools such as observation sheets for children and teachers and the test as an evaluation material at the end of each cycle that aims to determine changes in the ability of children to develop affection in the fairytale method. There are several conclussions: The level of affection of children in Cycle I there were 18 children  66.67%) reached the level of completeness ≥ 70, this means the child had not reached classical completeness and was in the Fair criteria. While in Cycle II there were 23 children who had reached mastery levels ≥ 70 (85.18%). So in Cycle II an increase in affection which has reached the Good category.